2018
DOI: 10.1371/journal.pone.0196100
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of fish oil with palm oil: Effects on growth performance, innate immune response, antioxidant capacity and disease resistance in Nile tilapia (Oreochromis niloticus)

Abstract: This study was conducted to investigate the effects of replacing dietary fish oil (FO) with palm oil (PO) in juvenile Nile tilapia, Oreochromis niloticus (9.34± 0.02g initial weight) with emphasis on growth performance, digestive enzyme activities as well as serum biochemical parameters. Also, lysozyme activity (LYZ), respiratory burst (RB), superoxide dismutase (SOD), catalase (CAT) and resistance to Streptococcus iniae were investigated. Fish were stocked in 15 rectangular fiber glass tanks (150× 60× 40 cm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Exposed liver cells of Oreochromis niloticus to diclofenac (DCF) for 30 days showed activity of CAT inhibited, GSH level decreased and the increase in the activities of SOD and GST [62]. Results of actual study are different from other studies where serum malondialdehyde (MDA) activity was significantly reduced while activity of glutathione reductase significantly increased and no significant for CAT, SOD activity compared to control of Nile tilapia after 56 days [63]. N-acetyl cysteine (NAC) caused decreasing activity of MDA in liver, increasing activity of GST in plasma and activity of SOD increased in liver of Oreochromis niloticus after 8 weeks [64].…”
Section: Resultsmentioning
confidence: 57%
“…Exposed liver cells of Oreochromis niloticus to diclofenac (DCF) for 30 days showed activity of CAT inhibited, GSH level decreased and the increase in the activities of SOD and GST [62]. Results of actual study are different from other studies where serum malondialdehyde (MDA) activity was significantly reduced while activity of glutathione reductase significantly increased and no significant for CAT, SOD activity compared to control of Nile tilapia after 56 days [63]. N-acetyl cysteine (NAC) caused decreasing activity of MDA in liver, increasing activity of GST in plasma and activity of SOD increased in liver of Oreochromis niloticus after 8 weeks [64].…”
Section: Resultsmentioning
confidence: 57%
“…You et al (2019) reported that compared with fish oil, soybean oil and linseed oil significantly decreased the amylase and lipase activities of golden pompano (Trachinotus ovatus). Moreover, the replacement of FO with VO can significantly alter the lipase and amylase activities of Nile tilapia (Oreochromis niloticus) (Ayisi, Zhao, & Wu, 2018) and Yellowtail kingfish (Seriola lalandi) (Bowyer, Qin, Adams, Thomson, & Stone, 2012). However, feeding gilthead seabream (Sparus aurata) VO diets had no effect on its digestive enzymes (Castro et al, 2019).…”
Section: Replacement Of 100% Of Fo With Vos Significantly Decreases Pmentioning
confidence: 99%
“…Effects of replacing fish oil with palm oil have been reported and discussed conclusively in Ayisi et al (2018), a study directly related to this study. Additional file 1: Table S1 briefly shows how replacing palm oil with fish oil affected growth and feed utilization.…”
Section: Growth Performancementioning
confidence: 76%